Comparisons of air-conduction hearing thresholds between manual and automated methods in a commercial audiometer - Hui Liu; Hui Liu; Xinxing Fu; Xinxing Fu; Xinxing Fu; Xinxing Fu; Mohan Li; Mohan Li; Shuo Wang; Shuo Wang (Frontiers in Neuroscience, 2023)
ObjectiveTo investigate the correlation of air-conduction thresholds between automated audiometry in a non-isolated environment and manual audiometry in participants with normal hearing and different degrees of hearing loss.MethodsEighty-three participants aged 11–88 years old underwent automated pure-tone audiometry in a non-acoustically isolated environment, and the results were compared with those of manual pure-tone audiometry performed in a standard acoustically isolated booth, with the order of testing randomised. Six frequencies of 250, 500, 1,000, 2000, 4,000 and 8,000 Hz were tested.ResultsAll 166 ears were completed and 996 valid hearing threshold data were obtained, with 28 data exceeding the 95% confidence interval in the Bland–Altman plot, accounting for 2.81% of all data. The means and standard deviations of the differences for the six frequencies from 250 to 8,000 Hz were, respectively, 0.63 ± 5.31, 0.69 ± 4.50, 0.45 ± 4.99, 0.3 ± 6.2, −0.15 ± 4.8, and 0.21 ± 4.97 dB. The correlation coefficients of the two test results for normal hearing, mild, moderate, severe and above hearing loss groups were 0.95, 0.92, 0.97, and 0.96, respectively. The correlation coefficient of the automated and manual audiometry thresholds for the age groups under 40 years, 40–60 years, and 60 years above, were 0.98, 0.97 and 0.97, respectively, with all being statistically significant (p < 0.01). The response time of the three age groups were 791 ± 181 ms, 900 ± 190 ms and 1,063 ± 332 ms, respectively, and there was a significant difference between the groups under 40 years and over 60 years.ConclusionThere was good consistency between automated pure-tone audiometry in a non-acoustically isolated environment and manual pure-tone audiometry in participants with different hearing levels and different age groups.